Endobronchial tuberculosis mimicking pulmonary neoplasm - Abdul Rani, Mohammed Fauzi; Abdul Samad, Humairah; Ahlawat, Sunita (Faculty of Medicine, International Islamic University Malaysia, 2002)
A 64-year-old Chinese lady presented to us with three months history of chronic dry cough and weight loss without haemoptysis. There was no fever. She had never smoked. Initial chest x-ray (CXR) and thoracic CT showed left upper lobe collapse for which she underwent bronchoscopy. The appearance was suggestive of submucosal tumour. She needed a second bronchoscopy that showed caseating granuloma and smear positive for tuberculosis. She made good clinical recovery with anti tuberculosis treatment but review CXR at four months showed a mass lesion in the left apex for which she underwent fine needle aspiration cytology. This showed healing granuloma compatible with tuberculosis. This case was unusual to us because it had led us to believe that we were dealing with malignancy twice.